2015
DOI: 10.1002/elps.201500052
|View full text |Cite
|
Sign up to set email alerts
|

Environmental metabolomics: Biological markers for metal toxicity

Abstract: Environmental metabolomics is an emerging field referred to the application of metabolomics to characterize the interactions of living organisms with their environment. In this sense, the importance of monitoring the effects of toxic metals on living organisms has increased as a consequence of natural changes and anthropogenic activities that have led to an increase of toxic metal levels in terrestrial and aquatic ecosystems. For this purpose, the use of metabolomics based on MS to study metal toxicity is gain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 105 publications
0
26
0
Order By: Relevance
“…Undoubtedly, massive methods "the omics" are among the most efficient current tools. In this sense, it has been demonstrated that alterations of the homeostatic cycles are shown at the transcriptional level (transcriptomics) [93], by overexpression or inhibition of proteins (proteomics) [94] and by modifications of the metabolic cycles (metabolomics) [1,95]. On the other hand, it has been stated that approximately 1/3 of proteins need the presence of metals as cofactors to develop their function (metalloproteins) and that metals influence on more than 50% of the proteins [96].…”
Section: Omic Methodologies To Assess Health Effects Of Pesticides Anmentioning
confidence: 99%
See 2 more Smart Citations
“…Undoubtedly, massive methods "the omics" are among the most efficient current tools. In this sense, it has been demonstrated that alterations of the homeostatic cycles are shown at the transcriptional level (transcriptomics) [93], by overexpression or inhibition of proteins (proteomics) [94] and by modifications of the metabolic cycles (metabolomics) [1,95]. On the other hand, it has been stated that approximately 1/3 of proteins need the presence of metals as cofactors to develop their function (metalloproteins) and that metals influence on more than 50% of the proteins [96].…”
Section: Omic Methodologies To Assess Health Effects Of Pesticides Anmentioning
confidence: 99%
“…Thus, metallomics allows understanding the distribution of elements, concentration at equilibrium of free metallic ions or free elements in a cellular compartment, cell or organism [98] and refers to the identity and/or quantity of metals/metalloids and their species [99]. Likewise, it has been proposed the integration of a global (holistic) view, much more realistic of the processes that takes place in the environment [95].…”
Section: Omic Methodologies To Assess Health Effects Of Pesticides Anmentioning
confidence: 99%
See 1 more Smart Citation
“…New approaches in functional genomics and bioinformatics can help discriminate individual chemicals, or group of chemicals among complex mixtures that may contribute to adverse biological effects (Hook et al 2014). Furthermore, environmental metabolomics is an emerging field referred to the application of metabolomics to characterize the interactions of living organisms with their environment (García-Sevillano et al 2015). In Brazil, these approaches are still rare since gene expression was assessed only in 3% of studies.…”
Section: Biomarkers Used In Brazilmentioning
confidence: 99%
“…This may make metabolomics a sensitive tool for evaluating the effects of external stress than other omics techniques. Environmental metabolomics is an application of metabolomics in characterizing the interaction between organisms and the environment, which allows for us to assess the actual physiological state of an organism 16 . Although nuclear magnetic resonance (NMR) spectroscopy is the primary bioanalytical tool for detecting metabolites in environmental metabolomics, mass spectrometry (MS) is beginning to revolutionize the detection ability in this field due to its higher sensitivity 17 .…”
mentioning
confidence: 99%